2009
DOI: 10.1111/j.1469-8749.2009.03292.x
|View full text |Cite
|
Sign up to set email alerts
|

Ring 14 chromosome presenting as early‐onset isolated partial epilepsy

Abstract: We report four infants (two males, two females) with ring 14 chromosome presenting with early‐onset partial epilepsy. The first seizure occurred between 3 and 6 months (3, 3, 4, and 6mo respectively). In all four cases, diagnosis was based on early focal seizures, rather than on psychomotor retardation or morphological features, which were not prominent at seizure onset. Moreover, despite the young age of the patients and the high frequency of seizures, neither epileptic spasms nor progression to ‘epileptic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…In relation to seizure semiology and EEG findings, presentation of epilepsy in our cases seems to be similar to that reported by Ville et al [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In relation to seizure semiology and EEG findings, presentation of epilepsy in our cases seems to be similar to that reported by Ville et al [28].…”
Section: Discussionsupporting
confidence: 91%
“…Electroencephalogram pattern is even more variable than seizure semiology. Ictal recordings have been reported [16,21,22,25,28,29] and findings are heterogeneous, as in our cases. The occurrence of either diffuse or focal discharges is not surprising in epilepsies related to chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 47%
“…However, our patient is now seizure free following treatment. The relatively constant clinical feature of seizures may manifest in various forms [Schlade-Bartusiak et al, 2005;Ville et al, 2009;Zollino et al, 2009], and usually appears between 1 month and 4 years of age [Zelante et al, 1991;Shirasaka et al, 1992;Ono et al, 1999;Morimoto et al, 2003]. Also, both patients reported by Morimoto et al [2003] and Ono et al [1999] showed generalized tonic-clonic convulsions that are similar to our patient and others reported in the literature as drug resistant.…”
Section: Discussionsupporting
confidence: 84%
“…Also, both patients reported by Morimoto et al [2003] and Ono et al [1999] showed generalized tonic-clonic convulsions that are similar to our patient and others reported in the literature as drug resistant. Some ring 14 patients may have epilepsy without prominent psychomotor retardation or morphological features [Ville et al, 2009]. Interestingly, treatment resistant epilepsy is also a constant finding in ring chromosome 20 syndrome, in patients with and without detectable deletions, and regardless of the size of the deleted segment [Zou et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation